Kontribusi Motivasi dan Sikap Mandiri Terhadap Minat Berwirausaha Mahasiswa PKK FKIP UST - Rina Setyaningsih; Sri Wahyu Andayani (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2019)
The purpose of this study is to know the contribution of motivation and independent attitude towards entrepreneurship interest in Student. Type of quantitative research . Population of all students are taking entrepreneurship courses in the academic many as 152 students. Sampling technique with proportional random sampling is 92. Data collection using questionnaires and documentation. The data analysis technique for the first hypothesis test used double regression of two predictors, second and third hypothesis test using partial correlation and significance test using t-test. All requirements test meets analytical requirements (test of normality, linearity, and multicollinearity). The results showed motivation, independent attitude and entrepreneurship interest in the category was with average observations higher than the ideal average. Multiple regression analysis showed Freg= 87,821 with chance of error 0,000 double correlation coefficient Ry1,2= 0,820 and R2= 0,627 mean 62,7% entrepreneur interest can be explained by both predictor change, meaning effective contribution of motivation equal to 35,21% and independent attitude equal to 45.39%. Partial correlation coefficient R1y-2= 0,531 and R2y-1= 0,570.